A typology of counterinsurgency approaches towards ISIS-Allegiant insurgency groups: variations between the Western States and The Global South - Hlwatika, Vuyokazi Zintathu Maragaret (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2024.